The Oxford companion to modern poetry - Noel-Tod, Jeremy; Hamilton, Ian, 1938-2001 (Oxford : Oxford University Press, 2013)
'The Oxford Companion to Modern Poetry is an authoritative and accessible guide to the influential poets writing in English from 1910 to the present day. The A-Z entries explore the influences, inspirations, movements that have shaped the works and lives of these important authors. This major new edition has been expanded to include over 300 new entries covering a host of contemporary and international poets such as Don Paterson, John Kinsella, and Joy Harjo, in addition to updated entries on well-established figures such as T. S. Eliot and Carol Ann Duffy. This engaging and informative companion in a must-have for anyone with an interest in literature, and especially for poetry enthusiasts.'--Book Jacket.
Introduction to the Second Edition -- Introduction to the First Edition -- Selection of Anthologies -- Key to Contributors -- Companion to Modern Poetry -- Groups and Movements -- Lists of Prizes and Prizewinners -- General Web Links.
'First edition published as The Oxford companion to twentieth-century poetry in English, in 1994'--t.p. verso.
Includes bibliographical references.
Keywords: English poetry -- 20th century -- History and criticism; English poetry -- 21st century -- History and criticism; Poets, English -- 20th century -- Dictionaries; Poets, English -- 21st century -- Dictionaries; Poets, Commonwealth -- 20th century -- Biography -- Dictionaries; Poets, American -- 20th century -- Biography -- Dictionaries; Poets, English -- 20th century -- Biography -- Dictionaries; Commonwealth poetry (English) -- Dictionaries; American poetry -- 20th century -- Dictionaries